Corrosion Behavior of the Cu24Zn5Al Alloy in Sodium Sulfate Solution in the Presence of 1-Phenyl-5-mercaptotetrazole - Vojka Gardić; Žaklina Z. Tasić; Marija B. Petrović Mihajlović; Milan B. Radovanović; Milan M. Antonijević (Metals, 2023)
The results of this research on the electrochemical behavior of Cu24Zn5Al alloy in a 0.1 mol/dm3 sodium sulfate (Na2SO4) solution containing 1-phenyl-5-mercaptotetrazole (PMT) are presented in this paper. The influence of PMT concentration, chloride ion concentration, and pre-treatment were examined. The influence of pre-treatment was studied in terms of the effect of the immersion time of the electrode in the appropriate inhibitor solution. After selecting the optimal immersion time, its effect on the behavior of the Cu24Zn5Al alloy was tested in a 0.1 mol/dm3 solution of sodium sulfate in the presence of different concentrations of chloride ions. Research shown that with the increase of PMT concentration, the anodic current density around the corrosion potential decreases, indicating that PMT behaves as a corrosion inhibitor for Cu24Zn5Al alloy.